Interrogation of Enemy Airman (United States : Historic Film Classics, 1943)
A classified USAF training film, based on actual cases, that re-creates psychological techniques used to extract information from captured prisoners, including interrogations in German, Italian and Japanese.
Keywords: Documentary films